In-situ reconstruction of CoBOx enables formation of Co for synthesis of benzylamine through reductive amination - Zhang, Mingkai; Zhang, Sai; Ma, Yuanyuan (Frontiers in Chemistry, 2023)
Cobalt (Co) as a substitute of noble-metal catalysts shows high catalytic capability for production of the widely used primary amines through the reductive amination. However, the synthesis of Co catalysts usually involves the introduction of organic compounds and the high-temperature pyrolysis, which is complicated and difficult for large-scale applications. Herein, we demonstrated a facile and efficient strategy for the preparation of Co catalysts through the in-situ reconstruction of cobalt borate (CoBOx) during the reductive amination, delivering a high catalytic activity for production of benzylamine from benzaldehyde and ammonia. Initially, CoBOx was transformed into Co(OH)2 through the interaction with ammonia and subsequently reduced to Co nanoparticles by H2 under the reaction environments. The in-situ generated Co catalysts exhibited a satisfactory activity and selectivity to the target product, which overmatched the commonly used Co/C, Pt or Raney Ni catalysts. We anticipate that such an in-situ reconstruction of CoBOx by reactants during the reaction could provide a new approach for the design and optimization of catalysts to produce primary amines.